Cancer and Territory. A Journey through the Continuities and Spatial Discontinuities Projected by this Non-human Actor - Velásquez Árias, Milton César (Universidad del Rosario, 2020)
The present article focuses on unveiling the relationship between cancer and territory. This relationship arises in the understanding of how cancer, as a non-human social actor, affects the territorial construction of spaces in daily life from its conception and connotation to its management and use of space. We worked with ten cancer patients and ten specialists from an Oncology Unit, Oncólogos de Occidente, located in the coffee axis. We used a qualitative methodological strategy based on a phenomenological study that focuses on revealing the practices and discourses that objectify the new territorial configurations. Among the main findings is how the relationship between cancer and territory entails a novel perspective for contemporary territorial studies, which allows understanding territory as a social and cultural construction of the social actors that is not only gestated to the measure and signification of humans. Also, the territory is tailored by the non-human actors who come into dispute and in constriction with the very dynamics that facilitate the configuration and ordination of an appropriate space.